Manual for Minor Irrigation Works - Community Projects Administration, Planning Commission (Community Projects Administration, Planning Commission, Government of India, 1957)
The Manual for Minor Irrigation Works, issued by the Planning Commission, serves as a comprehensive technical and practical guide aimed at strengthening irrigation infrastructure within India’s community development framework. Recognizing the urgent imperatives of food security, population growth, and declining agricultural productivity, the manual integrates historical insights from ancient irrigation achievements with modern engineering standards to equip field officials with tools for surveying, designing, and maintaining minor irrigation systems. It systematically addresses crop water requirements, sources of irrigation such as rainwater, stream diversions, and groundwater, and outlines engineering specifications for embankments, canals, reservoirs, and diversion works. A significant advancement discussed in the accompanying research is A.N. Khosla’s theory of sub-soil flow, which challenged earlier assumptions by demonstrating that uplift pressures and exit gradients under weirs must be analyzed through streamline flow principles rather than simplistic linear paths; practical applications, including lessons from the Khanki Weir, underscore the importance of deep cutoffs and scientifically calculated flooring thickness to prevent structural failure. Beyond technical refinement, the document advocates a paradigm shift in the role of irrigation engineers—from rigid enforcers of standardized blueprints to collaborative facilitators working alongside cultivators—aligning irrigation expansion with the broader objectives of the National Extension Service and rural upliftment. Emphasizing maintenance, adaptability to soil and hydrological conditions, and community engagement, the manual positions minor irrigation not merely as an engineering enterprise but as a foundational instrument for sustainable agricultural growth, economic resilience, and participatory rural development in India.
Issued By : Community Projects Administration Planning Commission Govt. of India
Keywords: Minor Irrigation Works; Irrigation Engineering; Sub-Soil Flow Theory; Khosla’s Theory; Weir Design Principles; Uplift Pressure; Exit Gradient; Agricultural Productivity; Community Participation; Water Resource Management; National Extension Service; Rural Development